Brain Responses to Faces and Facial Expressions in 5-Month-Olds: An fNIRS Study - Di Lorenzo, Renata; Blasi, Anna; Junge, Caroline; van den Boomen, Carlijn; van Rooijen, Rianne; Kemner, Chantal (Frontiers in Psychology, 2019)
Processing faces and understanding facial expressions is a crucial skill for social communication. In adults, basic face processing and facial emotion processing rely on specific interacting brain networks. In infancy, however, little is known about when and how these networks develop. The current study uses functional near-infrared spectroscopy (fNIRS) to measure differences in 5-month-olds’ brain activity in response to fearful and happy facial expressions. Our results show that the right occipital region responds to faces, indicating that the face processing network is activated at five months. Yet sensitivity to facial emotions appears to be still immature at this age: explorative analyses suggest that if the facial emotion processing network is active this would be mainly visible in the temporal cortex. Together these results indicate that at five months, occipital areas already show face processing skills, while the facial emotion processing network seems not fully developed.